Creating entrepreneurial universities: organizational pathways of transformation - Clark, Burton R. (IAU Press, 1998)
Based on field research carried out over a two year period, this book describes processes of transformation that took place over a fifteen year period in five European universities. Five common features identified - described as "organizational pathways of transformation" - are highlighted and used to frame the case-study accounts. These pathways consist of: a strengthened steering core; an extended developmental periphery; a diversified funding base; a stimulated academic heartland; and an entrepreneurial culture. Taken together, these elements help universities overcome the growing imbalance between environmental demands and university capacity to respond that is now occurring in universities internationally. As universities come under greater pressure to change their traditional character and become more innovative and entrepreneurial, the successful implementation of new managerial perspectives is important if they are to succeed. Reconciling these changes with traditional academic values provide the concepts on which the case studies are based.